EMPLOYING JIGSAW IN ENGLISH ACADEMIC WRITING: AN ACTION RESEARCH IN AN EFL CLASS IN INDONESIA - Baron, Rifari (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
The aims of the study were to get increasing of students? English academic writing ability through the jigsaw technique. It is done in the English Education Program Study of Postgraduate Program Universitas Indraprasta PGRI Jakarta. In this study has emphasized teamwork learning. The research approach is mixed research using action research method. The process of collecting data used test, observation, documentation, interviews, and daily note. The technique of data analysis used qualitative analysis and quantitative analysis. The sample of the study is 20 students. The result of the study shown that the average score of the student English academic writing test is different. The average of the test in cycle 1 is 51.1, cycle 2 is 51,2 and cycle 3 is 79,6.Keywords: Academic Writing, English, Jigsaw Tujuan dari penelitian ini adalah untuk mendapatkan peningkatan kemampuan menulis akademik bahasa Inggris menggunakan teknik Jigsaw. Penelitian dilakukan di Program Studi Pendidikan Bahasa Inggris pada Program Pascasarjana Universitas Indraprasta PGRI Jakarta. Penelitian ini menitiberatkan pada pembelajaran kerja tim. Pendekatan penelitian adalah penelitian campuran menggunakan metode penelitian tindakan. Proses mengumpulkan data menggunakan tes, observasi, dokumentasi, wawancara dan catatan harian. Teknik analisis data terdiri dari analisis data kualitatif dan analisis data kuantitatif. Sampel penelitian sebanyak 20 mahasiswa. Hasil penelitian menunjukkan perbedaan nilai tes menulis akademik bahasa Inggris. Nilai rata-rata tes pada siklus 1 sebesar 51.1, siklus 2 sebear 51,1 dan siklus 3 sebesar 79,6..Kata Kunci: Menulis Akademik, Bahasa Inggris, JIgsaw